Rattus timorensis Kitchener, Aplin & Boeadi 1991 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
098. Timor Forest Rat Rattus timorensis French: Rat de Timor / German: Timor-Ratte / Spanish: Rata de bosque de Timor Other common names: Timor Rat Taxonomy. Rattus timorensis Kitchener, Aplin & Boeadi, 1991, 7 km east of Desa Nenas, 1900 m, Gunung Mutis, Timor, Nusa Tenggara, Indonesia. Phylogenetic affinities of R. timorensis are unclear, but based on albumin immunological analysis and unpublished allozyme electrophoresis, it is related to Komodomys rintjianus and Bunomys chrysocomus, although most closely to K. rintjianus. This implies that R. timorensis should be included in a different genus, particularly because its original description stated that its placement in Rattus is tentative. Rattus timorensis is known from a large fossil series on throughout Timor. There is another undescribed species of rat from Timor that is based on a single recently collected specimen. Monotypic. Distribution. Known only from type locality on W TimorI, Indonesia. Descriptive notes. Head—body 157 mm, tail 77+ mm, ear 20-5 mm, hindfoot 30 mm; weight 112 g. The Timor Forest Rat is small and distinctive, with soft and relatively long pelage. Dorsum is predominantly olive-brown, with dark brown guard hairs (guard hairs on rump tipped with light cinnamon buff) and hairs tipped with tawny olive. Sides are tawny olive, peppered with cinnamon buff that blends into light buff venter. Forefeet are white, and hindfeet are neutral gray withwhite toes, both being ocherous salmon ventrally. Ears are small, rounded, and dark gray; vibrissae are long. Tail length is unknown because type specimen’s tail is broken, but it is distinctly bicolored, neutrally gray dorsally and white ventrally, and covered with short hairs. Skull is smooth, with long rostrum compared with other species of Rattus. There are three pairs of mammae: one post-axillary and two inguinal. Habitat. Montane rainforest at elevations of ¢.1900 m (fossils found down to 500 m). Food and Feeding. No information. Breeding. No information. Activity patterns. No information. ...